The Rebellious No : Variations on a Secular Theology of Language - Vahanian, Noëlle, 1969- (Book collections on Project MUSE., 2014)
Beginning where the great masters of suspicion ended, this book aims for a renewal of theological thinking. Not by way of an argument against the death of God or on behalf of the postmodern return of religion, but instead by extending and radicalizing an iconoclastic and existentialist mode of thought. A theological thinking whose departure point assumes and accepts the critiques of religion launched by Nietzsche, Freud, Marx, and Feuerbach, but nevertheless takes theological desire seriously as a rebellious force working within, but against, an anthropomorphic, phallogocentric worldview.